O mal-estar docente em gestores escolares - Mazon, Cátia Xavier [UNESP]; Leite, Lúcia Pereira [UNESP] (My University, 2013)
This research aimed to identify and analyze the impact of stressful events associated with the school administrators in teacher malaise. 29 managers participated in his capacity as directors or deputy directors of the municipal system, the interior of São Paulo, with responses to the Inventory IMPIL (Evaluación Psicológica Del Estrés por InestabilidadLaboral - FIGUEROA; SCHUFER, 2006). The results indicate the presence of stressors in all areas assessed at different rates. The highest ranking stressors were concerns with health, emotional Diseases and economic concerns. The degree of discomfort tends to increase with age, but since the entry into this function. The extensive powers of management, indicate the occurrence of different degrees of impact between the groups, demonstrating that subjectivity needs to be considered for proposing improvements in working conditions and health organizations. Social changes, the demands of educational reforms and lack of recognition of the profession were associated with teacher malaise.

Esta pesquisa objetivou identificar e analisar o impacto de eventos estressores em gestores escolares associados ao mal-estar docente. Participaram 29 gestoras, na função de diretoras ou vice-diretoras de rede municipal, do interior do Estado de São Paulo, com respostas ao Inventário IMPIL (Evaluación Psicológica Del Estrés por Inestabilidad Laboral). Os resultados indicam a presença de estressores em todas as áreas avaliadas, em índices diferenciados. Os estressores de maior pontuação foram Preocupações com a saúde, Moléstias emocionais e Preocupações econômicas. O grau de mal-estar tende a aumentar com a idade, porém está presente desde o ingresso na função. As atribuições extensas da gestão indicam a ocorrência em graus diferenciados de impactos entre os grupos, demonstrando que a subjetividade deve ser considerada para a proposição de melhorias das condições e organização de trabalho. As transformações sociais aceleradas, as exigências das reformas educacionais e a falta de reconhecimento da profissão foram associadas ao mal-estar docente.
The malaise in teaching school director
El malestar docente endirectores de enseñanza escolar
Keywords: Malaise teacher; Professional stress; Conditions of teaching; School manager; Educational psychology; Mal-estar docente; Estresse profissional; Trabalho docente; Gestor escolar; Psicologia da educação